A System Dynamics Model for the Analysis of CO2 Emissions Derived from the Inclusion of Hydrogen Obtained from Coal in the Energy Matrix in Colombia - Insuasty-Reina, Jeniffer Guadalupe; Osorio-Gomez, Juan Carlos; Manotas-Duque, Diego Fernando (International Journal of Energy Economics and Policy, 2022)
The environmental effects generated by the energy sector worldwide have become increasingly evident, raising the concerns of governments, industries and the research sector for addressing this problem. In the search for alternatives, hydrogen technology has drawn attention for its benefits as a new energy vector, since it is highly efficient and clean, and has multiple sources of generation. In Colombia, the possible generation of this energy vector from coal gasification has been estimated, since coal is a resource that is abundant in the territory. However, as a technology that uses a fossil resource, an analysis of the environmental effects of its implementation is necessary. The present work uses a system dynamics model to analyse the carbon dioxide (CO2) emissions that would be generated in this process in the national context. Through simulation scenarios, a comparative analysis is carried out of the effects of the current use of coal within the energy matrix versus the use of this resource for hydrogen generation in the medium and long term. The results indicate that the implementation of this technology accompanied by a minimum CO2 capture process would represent a reduction in the total emissions of the energy matrix.